Pertumbuhan dan Hasil Beberapa Varietas Padi Gogo Toleran Alumunium di Lahan Kering Masam Lampung Timur: Growth and Yield of Several Aluminum Tolerant Upland Rice Varieties in Acid Dry Land, East Lampung - Priyadi; Rianida Taisa; Dulbari; Rizky Rahmadi; Fajar Rochman (JURNAL AGRI-TEK : Jurnal Penelitian Ilmu-Ilmu Eksakta, 2023)
Aluminum stress is a limiting factor for crop production on acid dry land with a low pH. The objectives of this study were to evaluate aluminum-tolerant upland rice varieties in acid dry land. The study was carried out using a completely randomized block design (RCBD) consisting of 8 varieties, namely IR64, Inpago 7, Dodokan, Dod-Pup1, Situ Bagendit, Situ Bg-Pup1, Batur, Batur-Pup1, and 4 strains, namely 19 (PB5)-2, 20 (PB8)-1, 21 (PB15)-1, and 22 (PB16)-1. The results showed that the Situ Bagendit variety with the Pup-1 locus gave the highest yield per plot compared to other varieties and lines, namely 287.5 g. These results also correlate with the ability of the variety to withstand aluminum stress, with a tolerance value of 3.00 (rather tolerant).